Effectiveness of delivery mode of pharmacist intervention to improve medication adherence and clinical outcomes in people with depression: a systematic review - Yosi Febrianti; Ika Puspita Sari; Anna Wahyuni Widayanti; Diana Setiyawati (International Journal of Public Health Science (IJPHS), 2026)
Depression is a treatable mental health condition with various medication options available. For patients with major depressive disorder (MDD), adherence to antidepressants is essential for effective treatment. However, low medication adherence remains a significant challenge, particularly in individuals with depression. Pharmacists play a crucial role in managing these patients. This systematic review evaluated the impact of pharmacist-led interventions, focusing on the effectiveness of delivery modes (in-person vs. online) in improving medication adherence and clinical outcomes for patients with depression. Randomised and non-randomised controlled trials were included. Data were sourced from PubMed, Scopus, ScienceDirect, and Google Scholar using keywords such as "pharmacist intervention," "education," "medication adherence," "depression," and "medication compliance." Three reviewers independently screened and selected articles, and methodological quality was assessed using the Joanna Briggs Institute Randomized Controlled Trial Checklist. From an initial pool of 791 publications, 364 underwent a comprehensive review, and 14 met the inclusion criteria. The most successful interventions were those conducted face-to-face (83%), compared to those conducted through video and phone calls (16%). However, neither method could improve the severity of depression significantly. Pharmacist interventions can enhance patient adherence to antidepressant medication in patients with depression. Compared to virtual methods, face-to-face techniques are more effective at improving adherence. However, they were not able to improve the symptoms of depression.